Pemberdayaan Ibu Balita dan Kader Kesehatan dalam Inovasi Tumbuh Kembang Anak dengan “Gempita Coting” Mencegah dan Menangani Covid-19 serta Stunting - Nurlailis Saadah; Hilmi Yumni; Annasari Mustafa; Budi Yulianto; Jenita Donsu; Dyah Noviawati Setya Arum; Teta Puji Rahayu; Uswatun Khasanah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
In Pacalan Village in 2021 there are 14 stunted children, 11 are short, 3 are very short due to lack of nutritional intake and stimulation, improper parenting style, inadequate health at home. In addition, there are also quite complex problems in handling children related to the Covid-19 pandemic. This activity is a PPDS community service program (Healthy Village Development Program). This program is related to the role of universities in providing education and community assistance through Interproffesional Collaborations (IPC) and Interproffesional Educations (IPE). The aim of the activity is to create a healthy village through good habits for children, starting from educational play media, food consumed, and daily habits that support health. These activities were introduced as the GEMPITA COTING program (Playing Movement and Implementing Health Protocols in the Prevention of Covid-19 and Stunting). Forms of community service in the form of training and assistance regarding the implementation of the 5M health protocol for village communities, the use of media for playing board games for children, clean and healthy living behavior (PHBS), little doctors and trauma healing. This community service method involves 6 professions namely Nurse, Midwife, Environmental Health, Public Health, Psychology and Nutrition. The program targets are elementary school children, Covid working groups, sanitation, and health cadres. The results of community service are evaluated through monitoring evaluation and followed up by conveying the sustainability of the programs to the Head of Pacalan Village, Plaosan Health Center and the Magetan Health Office.